Leadership - Sadler, Philip (London, United Kingdom : Kogan Page Limited, 2003)
More than ever leadership is recognised as central to determining the success or failure of an organization. This book offers an important and incisive contribution to the current debate.
The nature of leadership -- Leadership and management -- Leadership qualities -- Leader behavior -- Styles of leadership -- Recruiting and selecting future leaders -- The development process -- Cultural and diversity -- Role models -- The new leadership -- Summing up
Includes bibliographical references and index.
Keywords: LEADERSHIP